The Jurnal Lazuardi - admin admin (Jurnal Lazuardi, 2019)
Text and context are two things that cannot be separated. Text always appears and exists, if there is a context. Text, whether oral, written, or nonverbal text always occurs because there is a context, both in the context of the situation and cultural context. The meaning and meaning of a text, not determined by the text, but by context. Therefore, every text requires the principle of analogy as a foundation. The meaning and meaning of the text will be given by text. Context is what gives meaning to each text. An object, event, event, and conversation that produces various forms of text, will be found meaning and meaning through the context in which the text is processed and produced. The meaning and purpose of each text is in its context. Every student is expected to be creative in composing text whose meaning and purpose can be found in context as a foundation.